Zazen or Not Zazen?: The Predicament of Sōtōshū's Kaikyōshi in Brazil - Rocha, Cristina (Japanese journal of religious studies, 2004)
In this paper, I discuss the establishment of Sōtō Zenshū missions in Brazil. I contend that the discourse on Zen that emerged from the writings of D. T. Suzuki and the Kyoto School to resist Western cultural hegemony not only fed the Zen boom in the West, but has more recently impacted on the Zen practice of some Japanese. I show that Japanese Sōtōshū kaikyōshi who catered to the (mostly) non-Japanese Brazilian community since 1968 embraced Suzuki's ideas on Zen wholeheartedly in Japan, prior to their arrival in Brazil. Thus, while these kaikyōshi praised zazen as the main Zen practice, others, who catered for Japanese-Brazilians, favored devotional practices. Their diametrically opposing attitudes towards zazen and rituals created conflicts, which were mirrored in their congregation. Here I will present the kaikyōshi side of the conflicts and their evolution through the years to reveal the way the JapaneseBrazilian and non-Japanese communities negotiated their place in the Busshinji temple in Sāo Paulo city.